THE BELOMORIAN ECLOGITE PROVINCE (EASTERN FENNOSCANDIAN SHIELD, RUSSIA): MESO-NEOARCHEAN OR LATE PALEOPROTEROZOIC? - M. V. Mints; K. A. Dokukina (Геодинамика и тектонофизика)
A critical discussion of competing models of the geodynamic nature (oceanic or continental subduction) and age (Meso-Neoarchean or Late Paleoproterozoic) of the eclogite facies metamorphism in the Belomorian eclogite province (BEP) is based on the systematic analysis of the sum of previously known and newly obtained data characterizing the geological structure of the Salma eclogite association and features of zircons from eclogites, including the isotopegeochronological and geochemical characteristics, composition and distribution of mineral inclusions. Regular changes in the REE trends and crystallization-recrystallization temperature of porous zircons in eclogite-metagabbro illustrate the sequence of magmatic and metamorphic events in the Meso-Neoarchean and Paleoproterozoic. The susceptibility to recrystallization of zircons is due to partial metamictness and porous structure. The earliest (~2.9 Ga) zircon zones retain mag-matic-type REE trends. The microinclusions of the prenite-pumpelliite and greenschist facies minerals and the increase in the LREE and MREE concentrations indicate hydrothermal metamorphism in the spreading ridge and on the ocean floor at 2.9–2.82 Ga. Prenite, pumpelliite, albite, actinolite, chlorite, diaspore and saponite also form inclusions in the eclogitic garnet. An increase of LREE and MREE, the disappearance of the Ce positive anomaly, a change from negative to positive Eu anomaly at 2.82–2.78 Ga indicate that plagioclase was removed during the formation of the ‘garnet + omphacite’ eclogite association and the replacement of sphene with rutile. The eclogite facies metamorphism linked with subduction of the oceanic crust is also indicated by the microinclusions of garnet and rutile in zircon. The crystallization temperature in 700–900 °C range of the round-oval zircons from eclogites-metagabbronorites records the Neoarchean granulite facies metamorphism at 2.77–2.70 Ga, the negative Eu anomalies in the cores and rims of zircons indicate the participation of plagioclase in the metamorphic crystallization. Late (2.1–1.7 Ga) rims of porous zircons that occurred at 600–680 °C are distinguished by minimal REE concentrations, a change from a positive Eu anomaly to a negative one, and the appearance of a negative Ce anomaly, which indicates the presence of plagioclase, reducing type of fluids and, accordingly, low water activity that is characteristic of high-temperature metamorphism under stretching condition and mantle-plume activity. The deep Sm-Nd system reworking in the Belomorian tectonic province, including BEP, at ~1.9 Ga was caused by the crustal heating that spread from the Lapland granulite belt border in the west-south-westward direction. The Lu-Hf system in zircon reworking with a significant increase in radiogenic Hf indicates the recrystallization of a long-existing garnet, in which a significant amount of radiogenic 176Hf accumulated by 1.9 Ga as a result of the 176Lu decay. This contradicts the earlier suggestion of the eclogite garnet primary crystallization in the late Paleoproterozoic (1.94–1.89 Ga).